Effect of Ethyl Methane Sulfonate on Regermination and Survival of Momordica cymbalaria Fenzl. Implications for Conservation and Mutation Breeding of a Rare Medicinal Plant - Dipak V. Kumbhar,; B. K. Avchar, (The Bioscan, 2025)
Momordica cymbalaria Fenzl.is a rare medicinal plant with notable pharmacological potential, but its conservation and propagation are challenging due to limited seed viability and low germination rates. This study investigates the impact of ethyl methane sulfonate (EMS), a chemical mutagen, on the regermination and survival of M. cymbalaria. Tubers were treated with varying concentrations of EMS (10 mM to 50 mM) for different durations (4hrs, 6hrs, and 8hrs). Germination rates, survival, and morphological abnormalities were systematically recorded. Results revealed a concentration-dependent response to EMS treatment. Low concentrations of EMS enhanced germination rates suggesting a stimulatory effect on viability. In variance, higher concentrations remarkably reduced survival rates and induced morphological abnormalities. These findings highlight the dual role of EMS as both a germination enhancer at lower concentrations and a potent mutagen at higher concentrations.